2020
DOI: 10.1080/10803548.2020.1795374
|View full text |Cite
|
Sign up to set email alerts
|

Local knowledge of risks associated with artisanal small-scale mining in Ghana

Abstract: Artisanal small-scale mining is associated with disease, injury, environmental and social risks. These risks negatively impact human health and the environment. This study assesses miners' awareness and perceptions of the risks associated with their activity in three main districts in Ghana. Using the convenience sampling approach, 148 miners participated in the study in addition to key informant interviews and focus group discussions. The study revealed that the miners were generally not aware of the risks as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…It also includes every form of harm against the miners, mining communities, and resources located within the mining environment. This set of rules is mandatory and must be enforced by every player within the mining and mineral business [41,42,44]. Research has shown that enacting an Act and introducing laws or policies to drive Nigeria's mining sector can strengthen the regulatory frameworks [40,41,43,44].…”
Section: Legal Regulatory and Institutional Framework Of Artisanal And Small-scale Miningmentioning
confidence: 99%
See 2 more Smart Citations
“…It also includes every form of harm against the miners, mining communities, and resources located within the mining environment. This set of rules is mandatory and must be enforced by every player within the mining and mineral business [41,42,44]. Research has shown that enacting an Act and introducing laws or policies to drive Nigeria's mining sector can strengthen the regulatory frameworks [40,41,43,44].…”
Section: Legal Regulatory and Institutional Framework Of Artisanal And Small-scale Miningmentioning
confidence: 99%
“…This set of rules is mandatory and must be enforced by every player within the mining and mineral business [41,42,44]. Research has shown that enacting an Act and introducing laws or policies to drive Nigeria's mining sector can strengthen the regulatory frameworks [40,41,43,44]. However, there were no prior works on health, mine safety, and mining hazard prevention procedures until March 2016, when the Nigerian government acknowledged mercury and lead (Pb) health risks.…”
Section: Legal Regulatory and Institutional Framework Of Artisanal And Small-scale Miningmentioning
confidence: 99%
See 1 more Smart Citation
“…In Ghana, it is publicly known that artisanal miners operate in unsafe conditions which pose serious threats to everyone engaged in it [ 8 ]. The operations of artisanal miners present considerable amount of risks at an escalating rate [ 9 ]. The processes involved in this activity pose many occupational HSE hazards.…”
Section: Introductionmentioning
confidence: 99%
“…In Ghana, it is publicly known that artisanal miners operate in unsafe conditions which poses serious threats to everyone engaged in it [8]. The operations of artisanal miners present considerable amount of risk at an escalating rate [9]. The processes involved in this activity poses many occupational HSE hazards.…”
Section: Introductionmentioning
confidence: 99%